Ascendancy of youth tourism on the travel and tourism preferences - K.P, Vyshak; Nath B, Sabary; S. Nair, Sundeep; K. Sudhakaran, Aarathy (International Journal of Engineering and Technology, 2018)
Youth Tourism or Youth Travel in simplified terms deliberate out as the travel and touring plans followed by the population groups standing out between the age group of fifteen to thirty for a period ranging from more than one day and less than one consecutive year, making out on economical lines of stature to build out unique life experiences.The study is concentrated among the youth population of Kerala, who possesses a deliberate and distinguishing views on travel and touring idea. The study tries to evaluate the attitudes and choices of the youth on travel and tourism and to develop an authoritative model of their preferences. A focus is given on measuring the influence of youth on travel. And study also analyses the impact of tourism destinations on youth, and their preferences.Â Â